Investigating the interplay between organisational change and digital transformation healthcare - Geada, N.; Alturas, B.; Anunciação, P. (International Journal of Healthcare Technology and Management, 2024)
This paper explores the intersection of digital transformation and change management in healthcare organisations, emphasising the critical role of leadership. The study combines insights from a focus group with healthcare professionals and a bibliographic analysis of 308 Web of Science papers (20182022). Results indicate that change leadership is crucial for successful digital transformation, as technological innovation directly impacts change management processes. The literature review reveals a strong relationship between digital transformation and organisational change, addressing adoption, engagement, performance, and resistance. The focus group highlights inspirational leadership and process innovation as key mediators between leadership capabilities and organisational benefits. Participants consider digital transformation essential for healthcare strategy, improving diagnostic/surgical capabilities and overall performance. The study offers valuable insights into the dynamic interplay of leadership, technology, and change management, providing a foundation for future research and guiding practitioners on addressing emerging challenges in healthcare digital transformation.